ANALYSIS OF ADHERENCE TO TAKING HYPERTENSION MEDICATION OGAN ILIR REGENCY IN 2024 - Bara Yunita; Ali Harokan; Chairil Zaman (LPPM STIKES Al-Ma'arif Baturaja, 2024)
The prevalence of hypertension in Indonesia has increased by 34.1%, but it is quite unfortunate that of all hypertension patients there are 32.3% of people who do not regularly take medication and 13.3% who do not take blood pressure lowering medication. However, taking blood pressure-lowering medication regularly can reduce the risk of cardiovascular disease. This study aims to determine the factors associated with adherence to taking hypertension medication in the elderly at the Pegayut Community Health Center, Ogan Ilir Regency in 2024. . The design of this research is a quantitative analytical survey with a cross-sectional approach. The population of this study was 1788 elderly people with hypertension visiting the Pegayut Community Health Center, Ogan Ilir Regency in 2023, with a total research sample of 95 respondents. The sampling method uses purposive sampling technique, calculated using the Slovin formula. The sample criteria are being willing to be a respondent and not being sick. This research was carried out on 07-24 February 2024. The data collection used in this research was primary data which was collected by conducting interviews with respondents using a questionnaire tool. Bivariate data analysis used the Chi-Square test and multivariate logistic regression. Based on bivariate analysis, it is known that there is a relationship between gender (p value 0.022), motivation (p value 0.031) and officer role (p value 0.024). The most dominant factor in compliance with taking hypertension medication in the Pegayut Community Health Center Working Area, Ogan Ilir Regency in 2024, is gender (p value 0.00) (OR 45.2). The conclusion of this research is that there is a relationship between type, motivation and role of officers.